2011
DOI: 10.1007/s11709-011-0118-6
|View full text |Cite
|
Sign up to set email alerts
|

Unified calculation method and its application in determining the uniaxial mechanical properties of concrete

Abstract: This paper presents a unified calculation method and its application in determining the uniaxial mechanical properties of concrete with concrete strengths ranging from 10 to 140 MPa. By analyzing a large collection of test results of the uniaxial mechanical properties of normal-strength, high-strength and super high-strength concrete in China and performing a regression analysis, unified calculation formulas for the mechanical indexes of concrete are proposed that can be applied to various grades of concrete f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 109 publications
(94 citation statements)
references
References 2 publications
1
80
0
Order By: Relevance
“…Existing studies have indicated that the stress-strain constitutive model for RAC and normal concrete is very similar [2]. Accordingly, the measured RAC material properties obtained in the present experimental work were used in FE analysis, and the input stress-strain relation for RAC under uniaxial compression and tension used in the current FE analysis was determined from equations (1)-(4), which are given by [33] for normal concrete. e schematic diagram of the stress-strain relation for nonlinear structural analysis of RAC is shown in Figure 9.…”
Section: Materials Model For Racmentioning
confidence: 96%
“…Existing studies have indicated that the stress-strain constitutive model for RAC and normal concrete is very similar [2]. Accordingly, the measured RAC material properties obtained in the present experimental work were used in FE analysis, and the input stress-strain relation for RAC under uniaxial compression and tension used in the current FE analysis was determined from equations (1)-(4), which are given by [33] for normal concrete. e schematic diagram of the stress-strain relation for nonlinear structural analysis of RAC is shown in Figure 9.…”
Section: Materials Model For Racmentioning
confidence: 96%
“…m is a parameter that controls the decrease in the elastic modulus along the ascending portion of the axial stress-strain relationship and equals to ranging from 20 MPa to 140 MPa which has been validated by experimental results [13].…”
Section: Finite Element Modelingmentioning
confidence: 99%
“…The displacement loading mode was selected to solve the nonlinear equations. The material constitutive models of concrete used for this study were suggested by Ding et al [13]. In addition, Plastic-damaged model was adopted for the concrete.…”
Section: Finite Element Modelingmentioning
confidence: 99%
“…Table 3 shows the element type of the CFT component. Ding et al [16] and Liu et al [17] provided detailed modeling parameters and constitutive material models. Figure 7 presents the FE model of the CFT columns.…”
Section: Fe Modelingmentioning
confidence: 99%